The Effect of Varied Passing Drills on Improving Passing and Stopping Skills in the Abhiseva Branch Futsal Team in Bengkulu City - Irpan Ependi; Feby Elra Perdima; Mariska Febrianti (Educative Sportive, 2026)
This study aims to determine the effect of varied passing drills on improving passing and stopping skills in the Abhiseva Branch Futsal Team in Bengkulu City. The research method used was an experimental method with a one-group pretest-posttest design. The population in this study consisted of all 20 futsal players from the Abhiseva Branch in Bengkulu City. Total sampling was used, meaning the entire population served as the study sample. The research instrument was a futsal passing and stopping test. Data collection involved an initial test (pre-test), the implementation of the intervention—consisting of varied passing drills over 8 sessions—and a final test (post-test). Data analysis techniques included normality tests, homogeneity tests, and hypothesis testing using the t-test at a significance level of α = 0.05. Based on the research results, the pre-test mean score was 10.62 and the post-test mean score was 16.2, indicating an increase of 5.5. The results of the hypothesis test showed that the calculated t-value of 1.75 was greater than the critical t-value of 1.725 (calculated t > critical t), so the research hypothesis was accepted. Thus, it can be concluded that varied passing drills have a significant effect on improving passing and stopping skills in the Abhiseva Branch Futsal Team in Bengkulu City.